ANALISIS PROKSIMAT, SENYAWA FENOLIK, SIFAT ANTIOKSIDAN DAN ANTIBAKTERI KULIT BUAH Lepisanthes alata - Anton Rahmadi; Yuliadini Puspita; Desy Nursayekti; Ira Sintia Sinaga; Rica Oktalina; Herry Setiawan; Wiwit Murdianto (Jurnal Teknologi dan Industri Pangan, 2016)
Bengalun (Lepisanthes alata) is a rare and under-reported fruit native from the forests of Borneo. This fruit is non-seasonal with a thick skin and crimson color, therefore shows potential to be used as raw material for herbal tea. This research was conducted in three phases, namely: (1) to report proximate portions of seed, flesh and skin of the fruit, (2) to find the best combination of time and temperature of fruit skin drying, and (3) to explore the potential antioxidant and antibacterial capacity of fruit skin extracts produced in step (2). Proximate analysis carried out following oven-drying (60°C, 12 hours) and sun-drying (8 hours). Combination of oven temperature (40, 50, 60°C) and time (8,10,12 hours) was given to find the best drying treatment in terms of vitamin C, total phenols and anthocyanins. Anthocyanins levels approached qualitatively by red color absorbance (l=545 nm). The antioxidative capacity was approached with DPPH assay. Inhibition zones were measured against Staphylococcus aureus and Escherichia coli. Best drying treatment was at 60°C for 8 hours with moisture content of 6.73±0.18%, vitamin C of 76.9±3 mg/100 g, total phenols of 1112±8 mg GAE/kg, and red color absorbance of 0.259±0.060. The average IC50 antioxidant activity for the fruit skin extracts was 252.83±1.38 ppm. Ethanolic extract produced inhibition zones from 10.76% (1.0 mg extract/50 mL) to 22.77% (1.5 mg extract/50 mL), when compared to the positive control. Aquadest extract produced inhibition zones ranging from 7.99% (0.5 mg/50 mL) to 11.00% (1.5 mg/50 mL). N-hexane extracts showed no antibacterial activity.